Efficient Degradation of Aqueous Rhodamine B Irradiation Under Indoor Light Using a SiO2–Hypocrellin B Complex. (6th June 2016) - Zhang, Jucheng; Yan, Heping; Chen, Yashun; Chen, Rui; He, Ying; Liu, Wei
Abstract: An efficient method for the degradation of the dye Rhodamine B (RhB) is reported. A SiO2 –hypocrellin B (SiO2 –HB) complex was found to work as a catalyst to degrade RhB in aqueous solution at room temperature and atmospheric pressure, over the pH range 1–10, under indoor light conditions. This method is capable of removing 82.68% of RhB within 20 min at pH 9. The SiO2 –HB complex was characterized by both scanning electron microscopy and surface area analysis. The reaction progress was examined using ultrahigh pressure liquid chromatography/mass spectrometry and UV–visible spectroscopy. This process represents an efficient means of decontaminating dye‐containing wastewaters in either highly acidic or weakly alkaline environments. Abstract : The natural photosensitizer hypocrellin B (HB) was used to prepare a SiO2 –HB catalyst to degrade wastewater by an impregnation method. The results demonstrate that the SiO2 –HB complex is capable of rapidly degrading Rhodamine B (RhB) at room temperature and ambient atmospheric pressure in aqueous solutions with wide pH values ranging from 1 to 10, and under indoor light. And the SiO2 –HB complex appears to be an efficient catalyst for the degradation of the model dye RhB in wastewater and can be separated easily.